The Pau-paunna Indale Patara: Sufism And The Bugis Adaption And Transformation Of The Hikayat Inderaputera - Rahman, Nurhayati (Penerbit Universiti Sains Malaysia (USM Press), 2016)
The pau-paunna Indale Patara is a Bugis literary work about the vicissitudes and quest of a young prince, written in free prose style with beautiful language. The story is based on the well-known Malay hikayat Inderaputera, itself derived from an earlier Indian work, but was adapted and transformed by the Bugis in order to make it meaningful to their own society. In this article, I discuss various cultural concepts that the Bugis introduced and embedded within the story and manifest in the character of the hero, Indale Patara. In the story, these concepts interact with the mystical form of Islam that the South Sulawesi rulers converted to at the beginning of the 17th century. In particular, Ibn al-Arabi's concept of the "perfect man." I demonstrate the Sufi aspects of the story and show that only by combining Islamic and Bugis qualities and characteristics could Indale Patara become the perfect man.